(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
in this article, the issues of the classification of certain Timurid rulers in Rui González de Clavijo’s Diary of a trip to Samarkand – to the court of Amir Temur (1403-1406) are revealed scientifically analytically.